Pengolahan Limbah Cair Yang Mengandung Minyak Dengan Proses Elektrokoagulasi Dengan Elektroda Besi - Agung Prabowo; Gagah Hasan Basrori; P Purwanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Abstract Electrocoagulation is a coagulation method using direct electric current through an electrochemical event. This study aims to determine the possible use of electrocoagulation method as an alternative in wastewater treatment industry. This experiment uses waste oil content with the observed parameter is the change in concentration of organic material (COD. study was conducted on laboratory scale in batch by using a 3 iron plate measuring 3x5 cm 2 as anode and 3 aluminum plates of the same size as the cathode. Variations performed on current density, electrocoagulation time and distance .. Distance electrode plate electrodes used were 2 and 3 cm. Analysis of the samples carried out after the first sample was deposited for 30 minutes. Laboratory analysis refers to the SNI 06-6989.2-2004 for the parameters COD,. The analysis shows that there allowance for the highest percentage COD is 29, 83% occurred at minute 120, 32 A/dm2 current density, with an electrode distance of 2 cm .. In general these experiments show on a laboratory scale in batch conditions, electrocoagulation method effective enough to treat waste compared oil content with conventional coagulation process.